(untitled) (Revista de Estudios Europeos, 2026)
The incorporation of the then novel regime of criminal liability for legal persons calls into question the validity of the right to remain silent (or nemo tenetur) of these subjects in criminal proceedings, for several reasons. First, it is a fundamental right of a highly personal nature and closely related to the dignity and privacy of the passive subject, both of which are absolutely predicable with respect to legal persons. Second, the objective and subjective scope of this right is not clearly defined, which ultimately raises problems of applicability in the judicial phase. The issue requires a review of European case law and comparative law in order to obtain a global view of the matter, formulate proposals de lege ferenda that will allow progress to be made on the issue, and thus draw clearer contours of corporate nemo tenetur.